THE GASTROPODS DIVERSITY IN MANGROVE OF THE KECAMATAN SUNGAI APIT KABUPATEN SIAK AS MEDIA LEARNING THE CONCEPT OF BIODIVERSITY SENIOR HIGH SCHOOL CLASS X - Jasmi Astuti Jasmi Astuti; Yustina '; Elya Febrita Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: To investigate the diversity of gastropods in the mangrove of the Kecamatan Sungai Apit Kabupaten Siak in April to December 2014. The results are used for the development of instructional media in the form of media objects directly in the form of wet preservation of the species are found. This research was carried out with 2 phases: phase field research and media development. Determination of the research station by purposive sampling to establish three research stations. Each station consists of two transects and on each transect consists of 3 plots. Biological parameters observed that diversity index and the physical and chemical parameters include salinity, pH, temperature, organic content of the substrate and the texture class. The results showed that the diversity of gastropods in the mangrove forest area Apit Siak River District ranged from 1,73 to 1,82 which is relatively moderate range. The results of the research can be used as a medium of learning in the from of media preservation of biodiversity of the material wet grade ten senior high school.Keywords: Diversity Gastropoda, Mangrove, Media Learning.